Gambaran Depresi pada ODHA Perempuan yang Tinggal di Jakarta - Madyastha Aji Bhirawa (Universitas Katolik Indonesia Atma Jaya, 2016)
Indonesia is the one of the countries in the world with the epidemic transmission of HIV, which continues to grow. The transmission of HIV and AIDS is again related to risky of behavior and population key. In fact many couples who are contracting a partner who had behavior risk. In Indonesia the number of women who are infected increases. This indicates the susceptibility of women to HIV infection and AIDS. This descriptive study aims to discuss the depression in ODHA women who live in Jakarta. The method used is qualitative with the interviews. The respondents involved in this research were two adult female ODHA which are beginning with the age of the 21- 40 years and suffer from depression in accordance with depression in BDI-II. Data analysis revelaed the different levels of depression that women were affected from their experienced problems, the disclosure status of HIV, the stigma and discrimination, and social support. In addition, the issues of this women who affected with HIV were parenting and caring family members and they were the person who support their families. From the two respondents this study discovered that both have negative thinking to themselves, experience, and future.Depression